Pengembangan Bahan Ajar Biologi SMA Kontesktual Berbasis Potensi Lokal Hutan Mangrove - Sukirno Sukirno; Setyoko Setyoko; Indriaty Indriaty (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The development of high school biology contextual teaching materials on biodiversity materials based on local potential in the Kuala Langsa mangrove forest aims to learn concepts in accordance with real environmental conditions, so that it will strengthen students' understanding of concepts and student interests. This research method is Research and Development (R&D), using the ADDIE development model (Analysis, Design, Development, Implementation and Evaluations). This research instrument uses a validation questionnaire of experts, practitioners and respondents' trials. The results of the validation by the teaching material expert validator amounted to 81.70% the category was very good and the qualifications were not revised. The practitioner validator was 83.3% in the excellent category and the qualifications of teaching materials were not revised. The results of the test of respondents in class X of SMA 4 Muhammadiyah Langsa obtained 80.28% achievement in the very good category. Based on the research, it was concluded that the development of contextual high scholl biology teaching materials based on the local potential of mangrove forest is suitable for use as biology teaching materials at SMA 4 Muhammadiyah Langsa on biodiversity material. Keyword: Biological Contextual Teaching Materials, Biodiversity, Local Potential.